Travel scholarship from Association for Computing Machinery Committee on Women - Parmaxi, Antigoni (My University, 2026)
Travel scholarship from Association for Computing Machinery Committee on Women for participation at the 3rd International Constructionism Conference 2014 in Vienna, Austria
Keywords: Sciences